Degradation of intestinal mRNA: a matter of treatment - Heumüller, Sabine; Sticht, Carsten; Kaiser, Karin; Wink, Elvira; Hagl, Cornelia Irene; Wessel, Lucas (World journal of gastroenterology, 2015)
AIM: To characterize the influence of location, species and treatment upon RNA degradation in tissue samples from the gastrointestinal tract., METHODS: The intestinal samples were stored in different medium for different times under varying conditions: different species (human and rat), varying temperature (storage on crushed ice or room temperature), time point of dissection of the submucous-mucous layer from the smooth muscle (before or after storage), different rinsing methods (rinsing with Medium, PBS, RNALater or without rinsing at all) and different regions of the gut (proximal and distal small intestine, caecum, colon and rectum). The total RNA from different parts of the gut (rat: proximal and distal small intestine, caecum, colon and rectum, human: colon and rectum) and individual gut layers (muscle and submucosal/mucosal) was extracted. The quality of the RNA was assessed by micro capillary electrophoresis. The RNA quality was expressed by the RNA integrity number which is calculated from the relative height and area of the 18 S and 28 S RNA peaks. From rat distal small intestine qPCR was performed for neuronal and glial markers., RESULTS: RNA obtained from smooth muscle tissue is much longer stable than those from submucosal/mucosal tissue. At RT muscle RNA degrades after one day, on ice it is stable at least three days. Cleaning and separation of gut layers before storage and use of RNALater, maintains the stability of muscle RNA at RT for much longer periods. Different parts of the gut show varying degradation periods. RNA obtained from the submucosal/mucosal layer always showed a much worse amplification rate than RNA from muscle tissue. In general RNA harvested from rat tissue, either smooth muscle layer or submucosal/mucosal layer is much longer stable than RNA from human gut tissue, and RNA obtained from smooth muscle tissue shows an increased stability compared to RNA from submucosal/mucosal tissue. At RT muscle RNA degrades after one day, while the stability on ice lasts at least three days. Cleaning and separation of gut layers before storage and use of RNALater, maintains the stability of muscle RNA at RT for much longer periods. Different parts of the gut show varying degradation periods. The RNA from muscle and submucosal/mucosal tissue of the proximal small intestine degrades much faster than the RNA of distal small intestine, caecum or colon with rectum. RNA obtained from the submucosal/mucosal layer always showed a much more reduced amplification rate than RNA from muscle tissue [β-Tubulin III for muscle quantification cycle (Cp): 22.07 ± 0.25, for β-Tubulin III submucosal/mucosal Cp: 27.42 ± 0.19]., CONCLUSION: Degradation of intestinal mRNA depends on preparation and storage conditions of the tissue. Cooling, rinsing and separating of intestinal tissue reduce the degradation of mRNA.